Behavioural text message reminders to improve participation in cervical screening: a randomised controlled trial. (November 2017) - Huf, Sarah; King, Dominic; Kerrison, Robert; Chadborn, Tim; Richmond, Adele; Cunningham, Deborah; Friedman, Ellis; Shukla, Heema; Tseng, Fu-Min; Judah, Gaby; Vlaev, Ivo; Darzi, Ara
Abstract: Background: About 4500 lives are saved annually in England through cervical screening. If all eligible women participated regularly, 83% of cervical cancer deaths could be avoided. Between 2011 and 2016, age-appropriate coverage (ie, screening within the previous 3·5 years for women aged 24–49 years or 5 years for those aged 50–64) fell from 75·7% to 72·6% nationally, and from 69·5% to 66·7% in London. Recent evidence showed that text message reminders (SMS-R) improved participation in breast and bowel cancer screening, and that SMS-R message content affects clinic attendance. We tested the effect of modifying SMS-R content on cervical screening uptake (ie, attendance after invitation) in a low-coverage London borough. Methods: Women aged 30 years and older, invited for screening from Feb 16, 2015, to Oct 5, 2015, were randomised (1:1:1:1:1:1:1 with a random number generator) to receive no SMS-R or one of six SMS-Rs: a simple reminder, general practice (GP) endorsement, total and proportional social norms messages (communicating screening rates of peers), and gain and loss-framed messages (lives saved and lives lost associated with participating in screening). Women aged 25–29 years were randomised (1:1) to no SMS-R or a GP-endorsed SMS-R. Recipients were masked to SMS-R content of other trial arms. The primary outcome was the proportion of women screened by 18 weeks, and analysis was by intention to treat with logistic regression, adjusted for age and Index of Multiple Deprivation decile. Ethics approval was obtained from South East Coast–Brighton & Sussex REC. This trial is registered withClinicalTrials.gov, numberNCT02363088 . Findings: 1568, 1522, 1493, 1514, 1488, 1560, and 1507 women aged 30–64 years were allocated no SMS-R, a simple reminder, GP-endorsement, total social norms, proportional social norms, gain-framed SMS-R, and loss-framed SMS-R, respectively. The greatest difference in uptake was between no SMS-R (34·4%, n=540) and GP endorsement (38·4%, 575) (odds ratio 1·19, 95% CI 1·03–1·38; p=0·02), followed by the simple reminder (38·1%, 580) (1·18, 1·02–1·37; p=0·03). No overall significant difference between the control and other trial arms was observed. Participation among the 1453 and 1482 women aged 25–29 years randomised to no SMS-R or a GP endorsement was 26·4% (384) and 31·4% (466), respectively (1·29, 1·09–1·51; p=0·002). No harms were observed. Interpretation: SMS-R messages improve cervical screening uptake. The behavioural sciences can inform the message content that has the biggest impact on screening participation. Funding: Imperial College Trust Charity, Public Health England